2020
DOI: 10.1002/jssc.202000255
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of supermacroporous cryogels with improved mechanical strength for efficient purification of lysozyme from chicken egg white

Abstract: A novel, facile, and robust strategy was proposed to increase the pore size and mechanical strength of cryogels. By mixing the monomers of acrylamide and 2‐hydroxyethyl methacrylate as the precursor, a monolithic copolymer cryogel with large interconnected pores and thick pore walls was prepared. Hydrogen bonding between the two monomers contributed to the entanglement and aggregation of the copolymers, thickening the pore walls and resulting in larger pore sizes. Analysis via mercury porosimetry demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Obviously, small amounts of VIM were polymerized into the poly(VIM‐HEMA) cryogel and large amounts of VIM were leached from the cryogel during the thawing step. This result further confirmed that functional monomers exhibited low copolymerization reactivity into cryogels 51 . However, in the system of VIM and MFC precursor, almost all VIM was polymerized into the poly(VIM)/MFC cryogel, demonstrating that MFCs contribute to the polymerization of VIM during the freezing process.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Obviously, small amounts of VIM were polymerized into the poly(VIM‐HEMA) cryogel and large amounts of VIM were leached from the cryogel during the thawing step. This result further confirmed that functional monomers exhibited low copolymerization reactivity into cryogels 51 . However, in the system of VIM and MFC precursor, almost all VIM was polymerized into the poly(VIM)/MFC cryogel, demonstrating that MFCs contribute to the polymerization of VIM during the freezing process.…”
Section: Resultssupporting
confidence: 71%
“…This result further confirmed that functional monomers exhibited low copolymerization reactivity into cryogels. 51 However, in the system of VIM and MFC precursor, almost all VIM was polymerized into the poly(VIM)/MFC cryogel, demonstrating that MFCs contribute to the polymerization of VIM during the freezing process. This is likely attributed to the physical confinement of nanofibrous MFC extruded by the formed ice crystals, which forces the VIM close to each other for the polymerization within the cryogel.…”
Section: Cyogels Fabrication and Characterizationmentioning
confidence: 94%
“…They are, already consolidated matrices, presenting a highly porous structure with a low resistance to flow. Furthermore, these materials have a versatility regarding their surface functionalization, which allows customizing the chromatographic process depending on the biomolecule of interest [17–19].…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of the large and interconnected channels in cryogels have been studied and reported elsewhere (Plieva et al, 2011;Carvalho et al, 2014;Baimenov et al, 2020;Sun et al, 2020). This material has a unique construction for separation purposes, especially when dealing with particulate-containing fluids such as cell homogenates and wastewater (Hajizadeh et al, 2014(Hajizadeh et al, , 2018Önnby, 2016;Srivastava et al, 2016).…”
Section: Characterization Of the Cryogelmentioning
confidence: 99%
“…The formation of such macroporous hydrogels, known as cryogels, at sub-zero temperature was reported ∼50 years ago (Lozinsky, 2002). The cryotropic gelation process can be summarized as following (Lozinsky et al, 1984;Carvalho et al, 2014;Sun et al, 2020), (a) the reaction mixture is frozen below the solvent crystallization point, which contains unfrozen microspheres and crystals of the frozen solvent; (b) the concentration of the precursors increases dramatically in the microspheres and begins the polymerization; (c) the frozen sections act as a pore-forming agent and form macropores after being melted; (d) the formed polymeric network is interconnected since the solvent crystals grow until they meet the facet of another crystal. The large interconnected channels in the matrix allow passing particulatecontaining fluids such as blood (Derazshamshir et al, 2010), wastewater (Önnby, 2016), cell suspensions (Zhou et al, 2015;Hajizadeh et al, 2018) with low backpressure.…”
Section: Introductionmentioning
confidence: 99%